2018
DOI: 10.1016/j.cobeha.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Bias in predicted and remembered emotion

Abstract: Predicting and remembering emotion both rely on the episodic memory system which is constructive and subject to bias. In keeping with the common cognitive processes underlying prospection and retrospection, people show similar strengths and weaknesses when they predict how they will feel in the future and remember how they felt in the past. Recent findings reveal that people predict and remember the intensity of emotion more accurately than their overall or general emotional response, and whether emotion is ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 53 publications
1
37
1
Order By: Relevance
“…Hogarth & Einhorn, 1992) and intense (e.g. Levine, Lench, Karnaze, & Carlson, 2018) emotional moments are better remembered. The finding that negative peaks received a slightly higher weight in mixed sequences suggests an influence of valence on memory that prioritises negative information.…”
Section: Discussionmentioning
confidence: 99%
“…Hogarth & Einhorn, 1992) and intense (e.g. Levine, Lench, Karnaze, & Carlson, 2018) emotional moments are better remembered. The finding that negative peaks received a slightly higher weight in mixed sequences suggests an influence of valence on memory that prioritises negative information.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotheses for the larger project are addressed in another paper (Lench et al, 2019). The main hypotheses for the current investigation were described in a published review (Levine et al, 2018) but analyses were not preregistered. The data are available online at https://osf.io/wh7kc/.…”
Section: Methodsmentioning
confidence: 99%
“…These cognitive biases often lead people to overestimate the overall emotional impact of both future and past events (Wilson et al, 2003). People show greater accuracy when the focus of attention is similar over time, such as when they predict or remember the peak intensity of their emotional response to events (Doré, Meksin, Mather, Hirst, & Ochsner, 2016;Kaplan et al, 2016;Levine, Lench, Kaplan, & Safer, 2012;Levine, Lench, Karnaze, & Carlson, 2018). Thus, common processes promote similar patterns of bias when people predict and remember their emotional reactions to events.…”
Section: Similarities Between Representations Of Future and Past Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…memory consolidation. Some empirical findings have shown that anxious individuals have attentional biases toward threats and that these biases affect memory consolidation [19,20]. Further, emotion-cognition interaction affects efficiency of specific cognitive functions, and that one's affective state may enhance or hinder these functions rapidly, flexibly, and reversibly [21].…”
Section: Introductionmentioning
confidence: 99%